Irish statute law reform - Jephson, Henry L. (Statistical and Social Inquiry Society of Ireland, 1879)
At the meeting of the British Association which was held in this city in August last, I had the honour of bringing before the Association the important subject of Irish legislation. In the paper that I read on that occasion, I endeavoured to establish the proposition, that it is desirable that the legislation for England and Ireland should be simultaneous, and as far as possible identical.
Read before the Society, 19 November 1878
Keywords: Irish statute law reform; Irish legal system; English legal system; 314.15